Human body composition - Singh S P; Gaur Rajan (Delhi Kamla-Raj, 2007)
This special issue of the Human ecology is devoted to the studies of human body composition. The papers presented in this issue explor numerous themes including the role of sitting height ratio of BMI and fatness, how physical activity changes body compo
Keywords: Anthropometry; Human body-composition